Development of squamous cell carcinoma at split-thickness skin graft donor site in a patient with burn injury - Victor Byers; Lisandro Montorfano; Lauren Sullivan; Jason Nolan; William Lineaweaver (Indian Journal of Burns)
Split-thickness skin grafts (STSG) are a mainstay of plastic and reconstructive surgery to provide autologous coverage for a range of acquired skin defects. The development of malignancies associated with STSG sites is rare but typically arises in the form of Marjolin ulcers over decades in the setting of chronic wounds and insults. However, a small number of case reports have identified new squamous cell carcinomas (SCCs) at STSG donor sites which arose in far shorter timeframes of weeks to months. Here, we describe an additional case of a SCC development at an STSG donor site in a 57-year-old male, treated for burn injuries after a house fire. A rapidly growing, exophytic lesion with ulceration was identified within 3 months of his original STSG anterior thigh donor site. Given the high concern for malignancy on presentation, he was treated directly with wide local, full-thickness excision of the mass, which was confirmed on pathology to be a well-differentiated, keratinizing-type SCC with clear margins. He was subsequently followed with serial physical examinations without the need for additional chemotherapy, radiation, or surgery for recurrence to date. Although unusual, SCC should remain on the differential of plastic and reconstructive surgeons when new lesions arise at STSG donor sites.